Effect of Proanthocyanidin, Fluoride and Casein Phosphopeptide Amorphous Calcium Phosphate Remineralizing Agents on Microhardness of Demineralized Dentin - Zahra Khamverdi; Matin Kordestani; Alireza Soltanian (Tehran University of Medical Sciences, 2017)
Objectives: The aim of this study was to evaluate the effect of dentin remineralization using proanthocyanidin (PA), fluoride varnish and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) paste and their various combinations on microhardness of demineralized root dentin. Materials and Methods: One-hundred and twenty freshly extracted sound human premolars were selected and randomly divided into eight groups for dentin treatment as follows. C: Deionized water (control); PA: 6.5% PA solution; F: fluoride varnish (5% NaF, 22600 ppm fluoride); CP: CCP-ACP; PAF: 6.5% PA + fluoride varnish; PACP: 6.5% PA + CCP-ACP; FCP: fluoride varnish + CCP-ACP and PAFCP: 6.5% PA + fluoride varnish + CCP-ACP. All specimens were subjected to Vickers microhardness test (500 g, 10 seconds, 3 points). Data were analyzed using one-way ANOVA and Tukey's post hoc test. The significance level was set at 0.05. Results: The mean and standard deviation (SD) values of Vickers hardness number (VHN) in groups C, PA, F, CP, PAF, PACP, FCP and PAFCP were 37.39±4.97, 38.68±4.62, 48.28±2.68 ,41.91±3.32, 48.59±2.55, 53.34±2.57, 48.413±4.00 and 55.20±1.82, respectively. Pairwise comparisons of the groups revealed that there was no significant difference between groups C and PA, PA and CP, F and PAF, F and FCP, PAF and FCP, and PACP and FPACP (P>0.05); but significant differences were observed between other groups (P<0.05). Conclusions: The results of this study showed that the tested dentin treatments increased the microhardness of demineralized root dentin except for PA application.